Desain Aplikasi Restoran Bakmi Ampo Berbasis Web - Aprizal Suryaman; Yoni Santoso; Muhammad Mayudin; Anang Mas Akmal; Teti Desyani (Program Studi Teknik Informatika Universitas Pamulang, 2021)
In this study, we will to solve the problem in a bakmi ampo restaurant that still uses manual methods to accept orders. As a result, many orders that come to customers are not suitable. We designed a web-based restaurant application to solve this problem. The method we use is the waterfall method, which is a systematic method for building software through various stages in SDLC. The reason for using the Waterfall method is because this method emphasizes the order in the software development process, after we tried to design the application design, the results were very effective in helping a bakmi ampo restaurant so that orders from customers were not wrong.